A VISIBILIDADE/INVISIBILIDADE DA FAMÍLIA HOMOPARENTAL NO CONTEXTO DAS ESCOLAS DO SISTEMA ESTADUAL DE ENSINO – NÚCLEO REGIONAL DE EDUCAÇÃO/PONTA GROSSA - ESTADO DO PARANÁ - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2017)
The affectivity is the component of the family bond that marks the new personalization of the Family Law and it opens the possibility of the recognition of the union of people of the same sex like family, with the paternity / maternity right. But there is still the image of the formation of the traditional patriarchal family, leaving this way the other settings invisible. Starting from the idea of the fundamental right of the child to the familiar living and considering the family and the school as members of the system of guarantees of the rights of the child and the adolescent, the research aims to observe the daily relations established by the school, as performer of the system of guarantees of the rights of the child and the adolescent, with the same-sex parents family. The hypothesis that guided the research is that in the school context the same-sex family is an invisible reality. The general aim is to analyze the way in which the schools of the state education system NRE / Ponta Grossa - State of Paraná work the demands of the same-sex family considering the school routine and the public policies of education. The research has a qualitative character, based on the hypothetical deductive method. The methodology used is the case study. The methodological course was the bibliographical, documental and the field research. In the field research the snowball approach was used to identify experiences of the same-sex parents family and its relation with the school, in the Regional Center of Education of Ponta Grossa-PR. The field data were collected through the: observation from; a semi structured interview; school documents such as the political pedagogical project, education plans, from the categories of the research. The interpretation and date analyses was done through the content analysis. The content analysis of the collected material was carried out considering the categories: school; family; diversity; same-sex parents family; system of guarantees for the rights of child and adolescents; education for diversity; stigma; stereotype; prejudice; discrimination; visibility / invisibility; exclusion. The results confirm the hypothesis of the invisibility of the same-sex parents family both in part of the legislation, or in the documents and in the school daily routine, demonstrating the challenges that are still present to the children and their families in order to guarantee the right of access and permanence of the child in the school. free from any form of violence originated from the prejudice and the exclusion. The research results showed that school does not know the history of its children, especially its family configuration and it has difficulty in understanding the contemporary family configurations, and it reproduces the hegemonic social patterns. The lack of inclusive practices in the school for the acceptance and recognition of the same-sex parents family results in a failure by the school in fulfilling its function of fully protecting the right of the child to familiar and community living as well as to education, confirming the hypothesis that guided the research, that in the school context same-sex parents family is an invisible reality.
Keywords: família homoparental; escola; políticas públicas da educação; invisibilidade/visibilidade; same-sex parents family; public education policies; school; invisibility / visibility; CNPQ::CIENCIAS SOCIAIS APLICADAS